Returns to education of manufacturing workers: Evidence from the People's Republic of China employer-employee survey - Hong Cheng; Hongbin Li; Li Tang; Zeyu Wang (Asian Development Bank Institute (ADBI), 2020)
Drawing on a random-sampling of matched employer−employee data that was collected in 2016 by the People's Republic of China Employer−Employee Survey, we first estimate returns of education for Chinese manufacturing workers. Using hourly wages as the dependent variable, we find that the estimated return to schooling was 5.1% within each firm, which is lower than that estimated by most recent studies based on the People's Republic of China's urban household survey data and the Chinese Population Census. After including education dummy variables in our regressions, we find that low returns to high school and vocational college are important factors to explain the low returns to education for Chinese manufacturing workers. Our between-group comparisons also show that educational inequality in less-developed regions and falling returns to female education are possible contributing factors to low returns to education. In addition, if the omitted ability characteristics can be fully controlled, then the true returns to education for Chinese manufacturing workers may become lower.
Keywords: I26; I25; E24; 330; education; manufacturing workers; employer-employee survey; People's Republic of China